Evaluating interactions between carbon sequestration and provisioning ecosystem services in Europe - Ivanov, Emil (2021)
This PhD study focused on research challenges associated with dependencies of human activities and wellbeing on the functioning of terrestrial ecosystems. It builds on the concepts of ecosystem services (ES) and natural capital accounting, applying a wider scope of actual or potential benefits to people but more specific recognition of the underlying ecological processes, expressed in a single measurement unit of carbon (gCm-2). The aim of the study is to evaluate how carbon sequestration and provisioning services interact and trade-off in spatially-explicit way across the European countries, applying carbon cycle and carbon budget approach. This was carried out through statistical analysis of ecosystems’ carbon budget at ground level and spatial modelling at seamless grid-level. Data quality and accuracy issues were encountered at both ground and grid levels and addressed through remote sensing vegetation indices. Because of the high correlation between NDVI (from MODIS) and GPP (from Fluxnet), the former was applied to detect sites with abnormal (outlier) GPP values and inconsistencies with other carbon budget variables. This allowed to ensemble a high quality ground dataset, and consequently to enhance the grid GPP estimates produced with the Vegetation Photosynthesis Model (VPM) of Zhang et al. (2017). Then, the ground carbon budget data was applied to train and validate a new grid estimation method based on VPM-GPP, Corine land cover, soil organic carbon (SOC) and a map of European ecoregions. This method was applied to map comprehensively the key carbon budget components including fluxes, harvests and flows. Finally, consistent NEP and NECB were mapped at 250m x 250m and were assessed against independent ground data from the published studies, which produced statistically significant Pearson correlation r = 0.72 for NECB and r = 0.73 for NEP. Provisioning ESs, including harvests of crops and fodder were mapped and assessed at aggregate regional level against European official statistics from EUROSTAT. The sum of the provisioning services was compared with carbon sequestration in soil and biomass to assess the main ESs trade-offs. The results revealed synergistic supply of services in areas of south and east Europe occupied by forests and other natural vegetation, permanent crops and less productive croplands. Most of the intensively cultivated crops and forestry areas of west and north Europe showed high provisioning ES rates traded-off against carbon sequestration ESs. Highest carbon losses were assessed for crops and pastures on organic soils under intense cultivations.